2021
DOI: 10.1038/s41422-021-00560-3
|View full text |Cite
|
Sign up to set email alerts
|

NudCL2 is an autophagy receptor that mediates selective autophagic degradation of CP110 at mother centrioles to promote ciliogenesis

Abstract: Primary cilia extending from mother centrioles are essential for vertebrate development and homeostasis maintenance. Centriolar coiled-coil protein 110 (CP110) has been reported to suppress ciliogenesis initiation by capping the distal ends of mother centrioles. However, the mechanism underlying the specific degradation of mother centriole-capping CP110 to promote cilia initiation remains unknown. Here, we find that autophagy is crucial for CP110 degradation at mother centrioles after serum starvation in MEF c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 63 publications
(87 reference statements)
2
22
2
Order By: Relevance
“…During starvation, the autophagic degradation of CP110 mediated by NudC-like protein 2 (NudCL2), a selective autophagy receptor at the mother centriole, induces cilium formation. This mechanism was confirmed also in Zebrafish models, where depletion of NudCL2 generates a ciliary phenotype that is rescued by CP110 depletion ( Liu et al, 2021 ).…”
Section: Autophagy Control Of Ciliogenesismentioning
confidence: 66%
“…During starvation, the autophagic degradation of CP110 mediated by NudC-like protein 2 (NudCL2), a selective autophagy receptor at the mother centriole, induces cilium formation. This mechanism was confirmed also in Zebrafish models, where depletion of NudCL2 generates a ciliary phenotype that is rescued by CP110 depletion ( Liu et al, 2021 ).…”
Section: Autophagy Control Of Ciliogenesismentioning
confidence: 66%
“…The past several years have illuminated the cross-talk between the primary cilium and the two major cellular catabolic pathways, i.e., the autophagic pathway and the ubiquitin proteasomesystem (UPS) ( Orhon et al, 2015 ; Pampliega and Cuervo, 2016 ; Boukhalfa et al, 2019 ; Wiegering et al, 2019 ; Morel et al, 2021 ; Morleo et al, 2022 ; Senatore et al, 2022 ). Many studies have demonstrated that autophagy is engaged in the regulation of ciliogenesis by controlling the expression of factors such as IFT20 ( Pampliega et al, 2013 ), OFD1 ( Tang et al, 2013 ), MYH9/myosin 2 ( Yamamoto et al, 2021 ), CP110 ( Liu et al, 2021 ) or Kif19A ( Arora et al, 2020 ). As such, the word “ciliophagy” has been adequately introduced to designate the selective degradation of ciliary proteins by the autophagic pathway ( Cloonan et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…NudCL2 also plays important roles for centriole duplication and sister chromatid cohesion by stabilizing the HECT and RLD domain containing E3 ubiquitin protein ligase 2 (HERC2) and the cohesin subunits during S-phase and prometaphase, respectively 32,47 . Additionally, NudCL2 acts as an autophagy receptor to promote ciliogenesis by mediating the selective degradation of centrosomal protein of 110 kDa (CP110) at mother centrioles 48 . However, whether NudCL2 is required for cytokinesis is still unknown.…”
Section: Discussionmentioning
confidence: 99%